Presence of Spontaneous Echo Contrast on Point-of-Care Vascular Ultrasound and the Development of Major Clotting Events in Coronavirus Disease 2019 Patients. (8th January 2021) - Connor-Schuler, Randi; Daniels, Lisa; Coleman, Caroline; Harris, Danny; Herbst, Nicole; Fiza, Babar
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: The presence of spontaneous echo contrast on ultrasonography is a predisposition to increased thromboembolic risk. The purpose of this study was to assess for the prevalence and consequences of spontaneous echo contrast on point-of-care vascular ultrasound in coronavirus disease 2019. Design, Setting and Patients: This was a retrospective cohort study of 39 adult patients admitted to the ICU with a confirmed coronavirus disease 2019 diagnosis at a large tertiary-care academic medical center. Patients were included if they had undergone a vascular ultrasound examination during their ICU admission. Overall, 48 venous ultrasound studies among the 39 patients were reviewed in blinded fashion by two reviewers for the presence of venous spontaneous echo contrast, and charts were analyzed for laboratory data and outcomes. Measurements and Main Results: S: pontaneous echo contrast correlated with serum viscosity (mean values of 2.64, 2.54, and 2.04 cP for dense spontaneous echo contrast, spontaneous echo contrast, and no spontaneous echo contrast, respectively, with a p value of 0.0056 for spontaneous echo contrast compared with negative spontaneous echo contrast) and hyperfibrinogenemia (mean values of 726.6, 668.5, and 566.6 mg/dL for dense spontaneous echo contrast, positive spontaneous echo contrast, and negative spontaneous echo contrast, respectively, with a p value of 0.0045 for dense spontaneous echo contrast compared with negative spontaneous echo contrast). About 36% of patients with dense spontaneous echo contrast and 33% of individuals with positive spontaneous echo contrast experienced significant clotting events compared with 17% of those with negative spontaneous echo contrast. A total of 19% of patients with spontaneous echo contrast suffered a cardiac arrest following a major clotting event, and there were no cardiac arrests from clotting events in the negative spontaneous echo contrast group. There was no association with the presence of spontaneous echo contrast and right or left cardiac function or other laboratory values such as d -dimer, external thromboelastometry - maximum lysis, platelet counts, C-reactive protein, or interleukin-6. Conclusions: Point-of-care venous ultrasonography is easily performed and reliably interpreted for visualization of spontaneous echo contrast. The presence of spontaneous echo contrast in patients with coronavirus disease 2019 is associated with hyperviscosity and increased rates of thrombotic events and complications.